Identifikasi Risiko Kesehatan dan Keselamatan Kerja pada Pekerja Pengumpul Sampah Manual di Jakarta Selatan - Dino Rimantho (Jurnal Optimasi Sistem Industri, 2015)
Waste collection is one of the activities that should be performed on the waste management process. This activity can pose a potentially high risk given the dangers that may arise while direct contact with the garbage and activities conducted. This study aims to identify potential risks to the health and safety of workers garbage collector. The survey uses a structured questionnaire distributed to 25 the refuse collector randomly selected in Srengseng SawahJagakarsa, South Jakarta. Descriptive statistics were used to analyze the data collected. The garbage collectors who agreed on the use of personal protective equipment at work is approximately 64% or around 16 respondents. Musculoskeletal disorders suffered by respondents is around 19 people or roughly 76%. The Respondents who suffered puncture wounds as a result of did not use gloves were 23 respondents or approximately 92%. Wrist and lower back are the most common musculoskeletal disorder that affects approximately 23 respondents. Generally, workers require personal protective equipment in order to prevent and reduce accidents. Improvement measures should be always be done such as healthy behavior, use of personal protective equipment and the development of working methods based on ergonomic principles.